Challenges of Global Health Security in pandemic times: The access to Personal Protective Equipment in the COVID-19 crisis - Pompeu, Eriton; Slovic, Anne (Saúde e Sociedade, 2023)
This article addresses the precariousness of the Global Health Security system, focusing on the distribution of Personal Protective Equipment (PPE) during health crises and taking the COVID-19 pandemic as a departure point and a center. The shortage of PPE was exacerbated by factors such as the high transmission rate of the virus, inadequate training on its use and disposal, flexibility in guidelines regarding prolonged use and reuse of equipment, and restrictions on the export of healthcare products. The collapse of the global PPE supply chain has exposed frontline healthcare workers, especially in low- and middleincome countries, due to inadequate healthcare infrastructure and socioeconomic disparities. The lack of effective action to maintain and equitably distribute existing PPE stocks further exacerbated their shortage, compromising the effective response to the pandemic. To strengthen the resilience of healthcare systems, strategies need to be developed to ensure safety and equity in the global supply chain of healthcare products, with interconnected and redundant networks of suppliers. International collaboration and investments in multilateral mechanisms play a crucial role in building a more resilient Global Health Security.